Working papers to accompany intermediate accounting : chapters 14-26, Miller, Searfoss and Smith - Barnett, Andrew H. (Illinois: Richard D. Irwin Inc., 1985)
This is a working papers to accompany intermediate accounting, chapters 14-26.
osa 22/01/19
Loans
Keywords: Accounting